Maintenance of Integrity of Upper Facet Joints during Simulated Percutaneous Pedicle Screw Insertion Using 2D versus 3D Planning - Archavlis, Eleftherios; Ringel, Florian; Kantelhardt, Sven (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background No studies have directly and quantitatively compared two-dimensional (2D) and three-dimensional (3D) planning as applied during conventional percutaneous or navigated percutaneous pedicle screw placement.Study Aims This lumbar pedicle-based stabilization simulation study aimed to investigate the risk of upper facet joint violation (FJV) during posterior percutaneous pedicle screw placement with conventional 2D planning of screw implantation (as a model for fluoroscopically guided screws) compared with 3D planning (as used with navigation techniques).Methods The placement of monosegmental lumbar pedicle screws using the data sets of 250 consecutive patients was simulated. Conventional surgery (using 2D fluoroscopic images anteroposterior and lateral view) was compared with screw placement using the 3D reconstruction of the planning mode of the same software.Results The 2D planning resulted in 140 upper FJVs (28% of cases), whereas 3D planning resulted in only 24 upper FJVs (4.8% of cases) (p < 0.05). Among those spinal segments with severe facet joint arthropathy, Pathria grades 3 and 4, FJV was significantly higher (p < 0.05) in the 2D-planned screws (64.7%) than in the 3D-planned screws (11.2%). A more lateral (mean distance: 3.5 mm) and inferior (mean distance: 2.5 mm) offset of the pedicle entry point and a larger medial angulation of the trajectory (mean angle: 9 degrees) were observed for the 3D-planned screws at all levels.Conclusion This study demonstrates that the use of 2D planning is associated with a higher risk of upper FJV than when a 3D imaging data set is used. Using a more lateral and inferior entry point for fluoroscopically guided pedicle screws could reduce the rate of FJV in percutaneous pedicle screw placement.
Keywords: pedicle screws; 3D simulation study; minimally invasive; facet joint violation; robotic